Implementasi nilai praksis Pancasila pada kehidupan sehari-hari - Annabilah, Fitri (Maliki Interdisciplinary Journal, 2024)
The application of Pancasila in millennial life today can be said to be very minimal, thus showing that Pancasila has a weak application and experience of Pancasila values. The writing in this article uses a literature study approach that utilizes facts with supporting sources such as ebooks, related journals, and predecessor articles. This paper is used as a study guide and life guide that regulates daily life by applying the values of Pancasila, and aims to make people aware of the importance of Pancasila values in daily life, so that people can apply it and practice it.